Educação escolar indígena: uma análise a partir da perspectiva da sexualidade e gênero no município indígena de Baía da Traição/PB - Silva, Patrícya Karla Ferreira e (2010)
The local Indians are an indigenous group that inhabits the northern coast of the Brazilian state of Paraiba, along with the limits of municipalities of Rio Tinto, Marking and Bay of betrayal. The Potiguaras not live entirely in a geographical isolation, social and cultural, since it appears the interaction between Indians and non-Indians in the territory of potiguaras. Therefore, this research aims to examine the expressions of sexuality and gender in adolescence Indian potiguaras inserted in school education in the city of Bay of Treason / PB from the perspectives of educators from the School Hall Elementary School Antonio Azevedo. The methodological approach includes quantitative and qualitative approach focused on data analysis. The study also required for the thematic analysis of the research object from the understanding of concepts such as: indigenous education, indigenous schools, indigenous education, and differentiated school, sexuality, and gender. The research is structured in three chapters that discuss about the theme. The first chapter presents a brief historical overview about the indigenous peoples, indigenous education, addressing also the structure of indigenous education in Brazil. The second chapter provides some discussions about sexuality and gender in indigenous education. The third chapter examines the indigenous education thematising an approach to sexuality and gender in the Bay of Treason / PB. It also points out the methodological issues for data analysis. In concluding this study, we realized the need to reflect on the schooling offered to indigenous people, especially in the gender and sexuality, considering the cultural background of these people and the process of miscegenation. Anyway, the question is: who will work as the differences in the sexuality and gender in school education. It will be just family, school or both.